Pedagogical Effects Of Moving (National) Game On The Process Of Physical Training And Education - М.Yu.Gafurova (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article argues that the pedagogical impact of mobile (national) play on physical education and learning process is that mobile games are a very effective tool in the process of physical education to bring up children in a healthy, active way through mobile games